PENGARUH EKSTRAK DAUN PEPAYA (Carica papaya) TERHADAP KEMATIAN LARVA NYAMUK Aedes agypti INSTAR III - Payangka, Jonathan; Risma, Risma; Wibowo, Prajogo (Jurnal Ilmu Kesehatan dan Kesehatan, 2019)
Background: Papaya leaves (Carica papaya) extract is a natural larvacide that contains papain and alkaloid karpain so its usage is safe for the environment. The larvacide properties can also be used to reduce the amount of Aedes aegypti mosquito larvae. This mosquito species is the main vector for the virus that causes dengue fever which incident number increases over the years. There have been a few methods used to control the mosquito’s amount, one of which is by decreasing the number of Aedes aegypti’s larvae using the organophosphate insecticide chemical known as temefos. Temefos is really effective in killing the Aedes aegypti larvae but it has a lot of side effects especially towards the environment. By controlling the number of the Aedes aegypti’s larvae, hopefully the number of the dengue fever case can also be reduced. Objective: To prove that the papaya leaves (Carica papaya) extract have effects on the death of Aedes aegypti’s instar III larvae. Method: This is an experimental research what uses a post test only control group design. The study consists of seven groups, which are positive control that is given abate powder, negative control that is given only aquadest, and five groups treated with concentrations of 0.5%, 1%, 1.5%, 2%, and 2.5%; repeated for four times. The calculation of the amount of dead larvae is done within the first 24 hours. Result: Based on the Kruskal-Wallis test, p’s value is <α with p value being 0.000 and α being 0.05. It proves the significance of the experiment. Conclusion: The papaya leaves (Carica papaya) extract have effects on the death of Aedes aegypti’s instar III larvae